Climate change 2014 : impacts, adaptation, and vulnerability. Part B: regional aspects (D2316) - Barros, V. R. Field, C. B., Dokken, D. J., Mach, K. J., & Mastrandrea, M. D. (USA : Cambridge University Press, 2014)
This latest Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) will again form the standard reference for all those concerned with climate change and its consequences, including students, researchers and policy makers in environmental science, meteorology, climatology, biology, ecology, atmospheric chemistry and environmental policy.
Includes annexures.
Keywords: Earth and Environmental Sciences, Climatology and Climate Change, Politics and International Relations, Comparative Politics